Anti-gallbladder cancer activities and toxicity studies of glycyrrhetinic acid derivative as a novel PPARγ agonist - Liu, Min; Ma, Haizhang; Xiong, Gaozhong; Qi, Mei; Xia, Yuan; Zhao, Yunxue; Ji, Chunyan; Sun, Juan; Sun, Tao (Frontiers in Immunology, 2025)
IntroductionChemotherapy remains the mainstay treatment for gallbladder cancer; however, its therapeutic efficacy is limited by poor chemosensitivity. Therefore, identifying more effective treatment strategies is essential for improving patient prognosis. In this study, we evaluated the antitumor activity of a novel PPARγ agonist, PG-4c, in gallbladder cancer and assessed its in vivo toxicity.MethodsHuman gallbladder cancer cells were treated with PG-4c to examine its effects on the cell cycle, apoptosis, invasion, migration, and intracellular apoptotic signaling. A xenograft tumor model was used to assess the antitumor efficacy of PG-4c in vivo. Toxicity associated with PG-4c was evaluated in both mice and zebrafish.ResultsPG-4c exhibited stronger anticancer activity than the standard chemotherapeutic agent gemcitabine. Its antitumor mechanisms involved inducing cell-cycle arrest, apoptosis, and necrosis through elevated intracellular reactive oxygen species levels and activation of cleaved caspase-3. PG-4c also impaired actin assembly, thereby inhibiting migration and invasion. In vivo, PG-4c significantly suppressed tumor growth in both zebrafish and mouse xenograft models. Notably, PG-4c demonstrated lower toxicity than the traditional PPARγ agonist pioglitazone, as supported by animal toxicity assays.DiscussionOur findings suggest that PG-4c holds strong potential as an effective chemotherapeutic candidate for gallbladder cancer. Given that PPARγ agonists are clinically approved drugs for dyslipidemia and diabetes, this class of agents may represent a promising new therapeutic approach for gallbladder cancer management.